The application of co-rotational approach in bond graph setting to the modeling of general spatial mechanisms undergoing large motions - Čohodar, M (Array, 2007)
The demand for higher operational speeds and longer, but lightweight, links in multibody systems such as robots, airplanes and other structural components typically leads to deterioration of the performance. Therefore the structural flexibility has to be taken into consideration. In this paper attention is focused on the dynamic analysis of the spatial multibody systems consisting of flexible beams undergoing large overall motions. Modelling of slender manipulator links that typically undergo large translational and rotational motion is not simple. There are several approaches that are developed. In this paper slender robotic links are modelled as collection of finite element beams based on co-rotational formulation. Bond graphs are well known as a powerful modelling methodology capable of dealing with systems of different physical domains. Using an object oriented approach and component models they can be used as a general approach for systematic development of complex engineering models. In this paper we extend the application a co-rotational formulation of bond graphs to modeling of general mechanisms consisting of flexible links treated as 3D beams. We also include the effect of gravity, which has previously been neglected. In this paper an absolute nodal coordinate formulation is analyzed and compared to the co-rotational approach. The emphasis is placed on applicability of the bond graph approach relative to other flexible body formulations. The results are illustrated by suitable examples.